Inducible Nitric Oxide Inhibitors Block NMDA Antagonist-Stimulated Motoric Behaviors and Medial Prefrontal Cortical Glutamate Efflux - Bergstrom, Hadley C.; Darvesh, Altaf S.; Berger, S. P. (Frontiers in Pharmacology, 2015)
Nitric oxide (NO) plays a critical role in the motoric and glutamate releasing action of N-methyl-D-aspartate (NMDA)-antagonist stimulants. Earlier studies utilized neuronal nitric oxide synthase inhibitors (nNOS) for studying the neurobehavioral effects of noncompetitive NMDA-antagonist stimulants such as dizocilpine (MK-801) and phencyclidine (PCP). This study explores the role of the inducible nitric oxide synthase inhibitors (iNOS) aminoguanidine (AG) and (-)-epigallocatechin-3-gallate (EGCG) in NMDA-antagonist induced motoric behavior and prefrontal cortical glutamate efflux. Adult male rats were administered a dose range of AG, EGCG or vehicle prior to receiving NMDA antagonists MK-801, PCP or a conventional psychostimulant (cocaine) and tested for motoric behavior in an open arena. Glutamate in the medial prefrontal cortex was measured using in vivo microdialysis after a combination of AG or EGCG prior to MK-801. Acute administration of AG or EGCG dose-dependently attenuated the locomotor and ataxic properties of MK-801 and PCP. Both AG and EGCG were unable to block the motoric effects of cocaine, indicating the acute pharmacologic action of AG and EGCG is specific to NMDA antagonism and not generalizable to all stimulant class drugs. AG and EGCG normalized MK-801-stimulated medial prefrontal cortical glutamate efflux. These data demonstrate that AG and EGCG attenuates NMDA antagonist-stimulated motoric behavior and cortical glutamate efflux. Our results suggest that EGCG-like polyphenol nutraceuticals (contained in “green tea” and chocolate) may be clinically useful in protecting against the adverse behavioral dissociative and cortical glutamate stimulating effects of NMDA antagonists. Medications that interfere with NMDA antagonists such as MK-801 and PCP have been proposed as treatments for schizophrenia.